Training profile counts for time-to-exhaustion performance - Basset, F. A.; Chouinard, R.; Boulay, M. R. (Canadian Journal of Applied Physiology, 2003)
The objective of this study was to compare the time to exhaustion (Tlim) at maximal aerobic speed (v.VO2max) in middle- and long-distance runners. Five middle-distance (MDR) and 5 long-distance (LDR) male runners, ages 28 +/- 7 years, were tested running on a treadmill, with the Universite de Montreal Track Test (UMTT), on maximal velocity and on time-to-exhaustion track tests. During the laboratory test, cardiorespiratory variables (e.g., HR, .VO2max, .VCO2, .VE) were assessed. Second, running velocity at .VO2max (v.VO2max) during the UMTT was determined and HR values were recorded; also, maximal velocity on a 30-m sprint (V30) and maximal heart rate (HR max) and time to exhaustion were determined on the track. No significant difference was observed between groups during the multistage treadmill test. Significant differences were found between groups for V30 and Tlim, with MDR showing a 23% longer running time than LDR. The results of the present study demonstrated that the training profile of middle-distance and long-distance runners plays a significant role in Tlim performance when v.VO2max is obtained during a test with short-duration stages.